Report of the Working Group on Posts Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2001)
The Tenth Five Year Plan (2002-2007) for the postal sector, formulated by the Working Group constituted by the Planning Commission, outlined strategic objectives and recommendations for transforming India’s postal system into a modern, financially viable, and service-oriented institution. The Working Group, chaired by the Secretary of the Department of Posts, focused on evolving long-term and short-term postal policies, achieving self-financing operations, and recommending institutional and structural reforms, including potential privatization and the creation of corporate bodies for insurance and commercial exploitation of postal assets. The Plan emphasized the provision of Universal Postal Services at affordable prices, enhancing administrative and financial autonomy, modernizing infrastructure, improving service quality to international standards, and generating revenues through new value-added products and services. The postal sector, influenced by global trends of deregulation and technological advancements, was projected to evolve into a comprehensive logistics and communication network, leveraging neighborhood branches as full-service distribution centers, integrating financial, printing, and information services, and facilitating e-commerce. The Plan envisioned the post office as a critical link between households, businesses, and the global supply chain, providing reliable door-to-door deliveries, enabling efficient collection and distribution of goods, and offering a range of consumer and financial services. By combining traditional mail with innovative products and technological capabilities, the postal system aimed to bridge the physical and virtual communication worlds, ensuring cost-effective operations, customer satisfaction, and sustained revenue growth.
Ministry of Communications Department of Posts
Keywords: Postal Sector; Five Year Plan; Universal Service; Postal Policy; Infrastructure Modernisation; Technology Integration; E-Commerce; Financial Viability; Local Distribution; Value-Added Services; Logistics; Customer Satisfaction